Pengaruh Tingkat Suku Bunga, Kualitas Pelayanan, dan Kualitas Produk Terhadap Kepuasan Nasabah Bank Perkreditan Rakyat Central Kepri - Suparwi Suparwi; Suparno Suparno; Hendri Herman (Jurnal Sains Sosio Humaniora, 2022)
This research aims to obtain information about the relationship between free variables, namely Interest Rates (X1), Service Quality (X2), and Product Quality (X3) with bound variables, namely Customer Satisfaction (Y) at the Central Kepri People's Credit Bank, both individually and together. The population of this study was all customers at the Central Kepri People's Credit Bank in January amounting to 400 respondents. In this study, there was no classification of customer differences based on type or group status, the two types of customers had the same treatment. Samples were taken using accidental techniques. Using the Slovin formula obtained a sample of 80 people. The results showed that there was a significant positive influence of Interest Rate (X1), Quality of Service (X2), and Product Quality (X3) on Customer Satisfaction (Y) as indicated by the calculated Fhitung value of 77,336. This value is much smaller than the calculated F value at the alpha significance level of 0.05 which is 2.72, or F = 77,336 < 2.72. The pattern of the relationship of the three variables expressed by the double regression equation = 2.928 + 0.314X1 + 0.418X2 + 0.309X3. If calculated per variable, then the variable that has the most influence is the accuracy variable, which has a coefficient of determination of 41.8%. This means that service quality is the factor that most affects Customer Satisfaction.